The video arts interactive catalogue (London : Video Arts, 1995)
video arts - world leaders in video training programmes
CD-ROM edition
Systems requirements : need for Multimedia PC or compatible with a 486-33 or higher processor, 8MB of RAM (recommended), 5MB of variable hard disk space, 8 bit sound card, double-speed CD-ROM Drive (300 Kb/sec), Super VGA Monitor (256 or more colours), Microsoft Windows 3.1 or later
Keywords: Video art -- Catalogs